2016
DOI: 10.1155/2016/6042967
|View full text |Cite
|
Sign up to set email alerts
|

Perception Study of Traditional Korean Medical Students on the Medical Education Using the Dundee Ready Educational Environment Measure

Abstract: Background. In Korea, a few studies regarding traditional Korean medicine (TKM) education have been conducted. The aim of this study is to evaluate students' perceptions regarding TKM education in Korea and compare them with those of other countries using a quantitative scale, Dundee Ready Educational Environment Measure (DREEM). Materials and Methods. We conducted a survey using DREEM in a TKM college. Totally, 325 students responded to this survey and we performed the descriptive statistics of scores in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
3
20
3
2
Order By: Relevance
“…In examining the sixth research question, is there a difference between male and female students in terms of the total score of the perception of atmosphere? In the present study, the score of men in the total score of the DREEM questionnaire is significantly higher than women, which is not consistent with the research of Altemani & Merghani (2017), Kossioni et al (2012), Edgren et al (2010), and Kim et al (2016).…”
Section: E Discussioncontrasting
confidence: 99%
“…In examining the sixth research question, is there a difference between male and female students in terms of the total score of the perception of atmosphere? In the present study, the score of men in the total score of the DREEM questionnaire is significantly higher than women, which is not consistent with the research of Altemani & Merghani (2017), Kossioni et al (2012), Edgren et al (2010), and Kim et al (2016).…”
Section: E Discussioncontrasting
confidence: 99%
“…These findings are consistent with the results of similar studies that found that those with higher scores on their learning environment had higher CGPAs. 7 - 9 , 36 , 40 Few studies showed a lack of relationship between students’ perceptions of the learning environment and their academic performance. 9 , 41 A study conducted in Pakistan to correlate students’ CGPAs and their learning environment indicated that CGPA does not have an enormous impact on the mindset of students.…”
Section: Discussionmentioning
confidence: 99%
“…Kim, et al 13 refieren en su anĂĄlisis, sobre ambiente educativo realizado en College of Korean Medicine, Kyung Hee University, que los estudiantes demuestran estrĂ©s en la vida universitaria e insatisfacciĂłn con el plan de estudios, hecho que se ve reflejado en el abandono de sus actividades extracurriculares 13 , situaciĂłn similar encontrada en nuestro estudio.…”
Section: Discussionunclassified